Inflation in Transition Economies : How Much? and Why? - Ghosh, Atish (IMF Working Papers; Working Paper, 1997)
Following very high inflation rates at the beginning of the reform process, most transition countries have succeeded in lowering their inflation to more moderate rates. Inflation rates in the Baltics, Russia, and other countries of the former Soviet Union are now typically in the range of 10-60 percent. This essay examines whether a further reduction in inflation may be necessary. It concludes that low inflation may be important for achieving remonetization of the economy and sustained output growth.